Perceptions of fairness in the psychological contracts of allied health professionals. Issue 2 (1st June 2015) - Flower, Rebecca; Demir, Defne; McWilliams, John; Johnson, Dianne
Abstract : Purpose: – The purpose of this paper is to investigate the relationships between components of the psychological contract, organisational justice, and negative affectivity (NA), with key employee outcomes (i.e. organisational commitment, job satisfaction, depression, and psychological distress) among allied health professionals. Design/methodology/approach: – In total, 134 (response rate of 46 per cent) Australian allied health professional completed a questionnaire. Findings: – Multiple regressions revealed that higher NA was associated with lower organisational commitment, lower job satisfaction, and higher levels of depression. The psychological contract variable, breach, was associated with depression. Informational justice was associated with organisational commitment. Distributive justice was associated with job satisfaction. Research limitations/implications: – This research is limited by its cross-sectional design and that the data were self-reported. The results obtained suggest the potential utility of collecting longitudinal data to replicate and extend the results. Practical implications: – While NA may be beyond management control, it may be ameliorated by attention to improving communication of management decisions and by sensitivity to the elements implicit in psychological contracts. The negative consequences of contract breach may be offset by informational and distributive justice. Originality/value: – This study is one of the first to examine multiple measures of the psychological contract in addition to organisational justice and NA. Further, this study adds to the literature for allied health professionals, where little is known about factors contributing to their turnover.